2005
DOI: 10.17221/4259-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Influence of growth rate, backfat thickness and meatiness on reproduction efficiency in Landrace gilts

Abstract: ABSTRACT:In the nucleus herd and subsequent multiplication herd of the Landrace (L) breed in 262 gilts farrowed after the first insemination we analysed the influence of various levels of average daily weight gain from birth in the performance test in the field (ADG1) and till mating (ADG2), average backfat thickness (mm) in the performance test (BF1) and at mating (BF2) or lean meat percentage (LM1 and LM2) on the age and weight at mating and at farrowing, on the number of piglets born, piglets born alive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Różycki (2003) proposed that result of the performance test was one of the main criteria in the selection of pig for breeding and livestock production. Some author use performance traits for the evaluation of growth ability, others use parameters from testing stations (Bečková et al, 2005;Kernerová et al, 2006;Michalska et al, 2014). Therefore, an evaluation of the livestock in advance is very important to know the conditions in which animal are kept before any definite recommendations can be made.…”
Section: Introductionmentioning
confidence: 99%
“…Różycki (2003) proposed that result of the performance test was one of the main criteria in the selection of pig for breeding and livestock production. Some author use performance traits for the evaluation of growth ability, others use parameters from testing stations (Bečková et al, 2005;Kernerová et al, 2006;Michalska et al, 2014). Therefore, an evaluation of the livestock in advance is very important to know the conditions in which animal are kept before any definite recommendations can be made.…”
Section: Introductionmentioning
confidence: 99%
“…Kerr and Cameron (1995) indicated that selection for lean growth on either an ad libitum or a restricted feeding regime did not significantly affect reproductive performance, while animals in lines with high lean feed conversion ratio or low daily feed intake had reduced reproductive performance. The results obtained by Bečková et al (2005) on a group of Landrace gilts suggest that reproductive performance is more determined by growth rate and backfat thickness than by meat content. On the other hand, according to other researchers there is no correlation between meatiness and reproductive performance traits such as fertility, the number of piglets born alive in a litter or the number of piglets reared (Čechová et al, 2000;Bocian et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…As a result, multiparous sows showed better productivity. Smaller fat reserves are undesirable, especially for primiparous sows (Amaral Filha et al, 2010;Bečková et al, 2005;Kawęcka et al, 2009;Roongsitthichai et al, 2011). Young females undergo ontogenetic changes and the production process (pregnancy and rearing of the litter) puts an enormous strain on their body; this concerns both multiparous sows and sows in the second reproductive cycle, which still undergo somatic development.…”
Section: Discussionmentioning
confidence: 99%
“…Body condition depends on nutrition and shows an association with reproductive traits (Beyga and Rekiel, 2010;Čechová and Tvrdoň, 2006;Maes et al, 2004;Young et al, 2004;Wähner et al, 2001). The correlations between growth rate, fat reserves and meat content at mating and reproductive results of gilts are known quite well (Amaral Filha et al, 2010;Bečková et al, 2005;Kawęcka et al, 2009;Roongsitthichai et al, 2011). Less study has been given to the issues concerning changes in fat reserves from high pregnancy to weaning, and their relationship with reproductive performance and rearing of piglets from primiparous and multiparous sows.…”
Section: Introductionmentioning
confidence: 99%